Perencanaan Sistem Penyaluran Air Hujan di Kawasan Pabrik Sepatu Kecamatan Lebaksiu Kabupaten Tegal - Eka Wardhani; Hanif Khudzaifah Hapsa (Jurnal Serambi Engineering, 2022)
The construction of the factory will increase the amount of rainwater into runoff. This will cause an increase in flood inundation downstream. The purpose of this study is to plan an environmentally sound drainage channel in a shoe factory area of 16 hectares. The research location is in Lebasiu Village, Lebaksiu District. This research begins with conducting a hydrological analysis to obtain the most suitable rainfall intensity to be applied at the activity location. The maximum daily rainfall data comes from the Pakubeureum, Kadipaten, Jatiwangi and Pesayangan Tegal rain observation posts. The calculation results show that the selected rainfall intensity is the Van Breen Method with the Talbot Equation approach. The calculation of the planned discharge is carried out using the Rational Method of 123.89 m3/second. The calculation of the channel dimensions is based on the Manning Equation, where the channel width is 1.5 m and the depth is 1 m. The width and depth of the planned channel is 1.5 m and the width is 1.5. Infiltration wells are planned at PT. X is a form of corporate responsibility in environmental management and implementation of environmentally sound development. The results of the calculation of the required infiltration wells are 17 units. The infiltration wells will be built scattered around the factory by taking into account the location and suitability of the factory building design. Rainwater from each factory building will be channeled through gutters to each of these infiltration wells.